Pancreatic adenosquamous carcinoma, a rare entity: report of four cases - Rui Jorge G. Almeida; Rui Pedro C. Oliveira; Helder D. Moreira; Bruno Filipe M. Fernandes; Pedro Gil B. Oliveira; Maria Augusta G. Cipriano (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Adenosquamous carcinoma of the pancreas (ASCP) is a rare variant of the pancreatic ductal adenocarcinoma (PDAC). Between 2004 and 2016, four cases of ASCP were resected at our institution; clinicopathological data were collected. All of our patients were males, aged 55-80 years. Three cases were cephalic tumors; and one, pancreatic tail tumor, measuring between 2.3 and 5.5 cm. All had neurovascular invasion and lymphatic metastasis. Two had retroperitoneal positive margins. The overall survival (OS) after surgery was three weeks-42 months. Prognosis of ASCP is dark and OS appears to be more closely related to surgical margins status than to other clinicopathological factors.